THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN DECISION MAKING AT THE TUTWURI HANDAYANI SCHOOL - Helina Apriyani (Sean Institute, 2022)
Schools as one of the education industries must be able to keep up with the speed of information. Quality schools can be seen from the results of the results. School programs are able to run well and achieve the goals that have been set by the school. This is certainly the implication of the application of management information systems in the framework of decision making by school management. This research is qualitative research or research. In general, qualitative research has two main characteristics, namely: First, data is not in the form of numbers, more in the form of narratives, stories, written documents and unwritten. Second, qualitative research has no absolute formulas or rules for processing and analyzing data. In the world of education, qualitative research aims to describe a process of educational activities that is based on the process of educational activities that is based on what happens on the ground as a study material to find its weaknesses and shortcomings so that it can be determined improvement efforts. In the face of globalization, the indonesian education world must immediately improve itself in improving information systems to support the competitiveness of human resources produced by these educational institutions. The information system that will be created must be balanced between the available technological infrastructure and its human resource capabilities so that there is no very far-reaching inequality and information systems cannot be significantly realized in supporting the quantity and quality of education fundamentally. In addition, information systems are increasingly needed by educational institutions, especially in improving the smooth flow of information in educational institutions, quality control and creating cooperation with other parties that can increase the value of educational institutions.